ANALISIS SIKAP TOKOH UTAMA DALAM ROMAN ANAK â€œFREUNDSCHAFT FÃœR IMMER UND EWIG ?â€ KARYA TILDE MICHELS - LYANA, CYNTHIA (IDENTITAET, 2016)
According to Thurstone, attitude was a form of feeling?s evaluation or reaction (Azwar, 2013: 5). In the Children?s novel, a character in the story shows the various attitudes that can be learning to the readers. The problem of this research: How is the attitude of the main characters in the children?s novel "Freundschaftfürimmer und ewig?" By Tilde Michels. The purpose of this research is to describe the attitude of the main characters in the children?s novel "Freundschaftfürimmer und ewig?" By Tilde Michels. This research is a descriptive qualitative research. In order to describe the attitude of the main characters, firstly the researcher identifies the character of main characters by using Sayuti?s characterization method. After that, the researcher uses the theory of analytical psychology of Carl Gustav Jung to analyze this research. Data which is related to the main characters and shows the attitude of the main characters are classified by the researcher such as through dialogues between characters, statements of the other, and the author. And, the result of this research shows that the main characters are Susi and Esther who have not only the extraversion attitude, but also have an introversion attitude. Through dialogue between characters, Susi shows extraversion attitude such as attention and curiousity. And She also has introversion attitude which is not easily influenced. Furthermore, by the statement of the other, Susi has extraversion attitude, which is attention. Meanwhile, through the author, Susi shows the introversion attitude, which is not easily influenced. And she also has the extraversion attitude, which is curious. It is contrast with Susi, through the dialogue between characters, Esther shows extraversion attitude such as initiative, emotional, and easily influenced. Furthermore, through the statement of the other, Esther shows the attitude of introversion such as arrogant or haughty. Meanwhile, through the author, Esther showed the extraversion attitude, which is can adjust herself and emotional. Keywords : Attitude, Children?s Novel, Michels